2019
DOI: 10.3390/ijms20143457
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of Trophoblastic-Derived Extracellular Vesicles in Regulatory T Cell Differentiation

Abstract: Regulatory T cells (Treg) are mandatory elements in the maintenance of human pregnancy, but their de novo differentiation has not been completely exposed. HSPE1 chaperone expressing trophoblast cells may have a role in it. Trophoblast-derived extracellular vesicles (EVs), either at the feto–maternal interface or in circulation, target CD4+ T cells. We hypothesized that HSPE1-associated trophoblastic cell line (BeWo)-derived EVs are active mediators of Treg cell differentiation. We proved at first that recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…Trophoblast-derived EVs were further shown to induce the differentiation of T cells into Treg (regulatory T) cells [55]. Treg cells exert a strong antigen-specific immunosuppression [47].…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%
See 1 more Smart Citation
“…Trophoblast-derived EVs were further shown to induce the differentiation of T cells into Treg (regulatory T) cells [55]. Treg cells exert a strong antigen-specific immunosuppression [47].…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%
“…Treg cells exert a strong antigen-specific immunosuppression [47]. The Treg induction was mediated by HSPE1 (heat shock 10kDa protein 1) carried by the EVs [55].…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%
“…Interestingly, this study demonstrated the presence of FasL and TRAIL arranged in aggregates on exosome surfaces which can relay death signals to interacting cells including T cells in vitro [ 87 ]. Further skewing T cell function toward an inhibitory phenotype, EVs released from BeWo cells, a choriocarcinoma cell line used to model trophoblast cells, promote differentiation of helper T cells to T regs and expansion of these anti-inflammatory cells through 10 kDa Heat Shock Protein expression [ 88 ].…”
Section: Placenta-derived Evs In Pregnancymentioning
confidence: 99%
“…However, this effect is not observed in syncytin‐2 (Syn‐2)‐silenced VCT exosomes, indicating an important function of exosomal Syn‐2 in immune suppression . Kovacs et al suggest that trophoblastic EVs act as important players in immune tolerance, which is associated with their regulation of T reg differentiation. Extracellular vesicle‐derived heat shock protein family E member 1 (HSPE1) promotes T reg differentiation from CD4 + T cells and T reg cell expansion in vitro .…”
Section: Evs In Normal Pregnancymentioning
confidence: 99%